SHP2 promotes the epithelial-mesenchymal transition in triple negative breast cancer cells by regulating β-catenin - Shihan Qian; Jingjing Zhu; Qing Han; Huang Cheng; Huaibin Zhou (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Growing evidence suggests that the tyrosine phosphatase SHP2 is pivotal for tumor progression. Triple-negative breast cancer (TNBC) is the most lethal subtype of breast cancer, characterized by its high recurrence rate, aggressive metastasis, and resistance to chemotherapy. Understanding the mechanisms of tumorigenesis and the underlying molecular pathways in TNBC could aid in identifying new therapeutic targets. Methods In this study, we conducted bioinformatics analysis of the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases to examine PTPN11 (encoding SHP2) expression levels and perform survival analysis in TNBC. Additionally, we analyzed SHP2 levels in four TNBC cell lines and a normal breast epithelial cell line using Western blot. Furthermore, we knocked down SHP2 expression via RNA interference in three TNBC cell lines. To assess the impact of SHP2 on invasion and migration, we conducted transwell assays and wound healing experiments. An in vivo experiment utilizing a mouse xenograft model was also performed to evaluate tumor metastasis. Moreover, we detected the expression levels of epithelial-mesenchymal transition (EMT) biomarkers and investigated the mechanism between SHP2 and β-catenin using Western blot and immunofluorescence experiments. Results We found that high SHP2 expression was associated with a poor prognosis in patients with TNBC. The migratory and invasive abilities of TNBC cells in vitro, as well as the metastatic potential of TNBC in mouse xenograft models, were reduced after SHP2 depletion. Downregulation of SHP2 also decreased the expression of mesenchymal markers but induced upregulation of the epithelial marker E-cadherin. Additionally, SHP2 promoted β-catenin stability by inhibiting its degradation via the proteasome. Furthermore, c-Myc expression and GSK3β and AKT phosphorylation, which are involved in β-catenin signaling, were decreased in SHP2-depleted TNBC cells. Conclusion Our study demonstrates that SHP2 is involved in migration, invasion, and EMT in TNBC cells by modulating β-catenin. Manipulating SHP2 expression or its target protein β-catenin may offer a novel approach to TNBC therapy.